2018
DOI: 10.1080/13816810.2018.1484928
|View full text |Cite
|
Sign up to set email alerts
|

The association of matrix metalloproteinases polymorphisms and interleukins in advanced age-related macular degeneration

Abstract: MMP1 rs1799750 1G/2G genotype was found to play a significant role in the development of eAMD at the age of less than 65 years. IL-1β concentration was significantly higher in eAMD patients for MMP1 rs1799750 1G/1G genotype and MMP7 rs11568818 A/G genotype compared with control group subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…Table 1 summarizes the polymorphisms of MMP genes that have been analyzed in AMD patients. Polymorphisms in MMP-1 (rs1799756) [30], MMP-3 (rs3025058) [26,32], and MMP-7 (rs11568818) [30,31] genes showed no statistical association with either the risk of AMD or disease progression.…”
Section: Matrix Metalloproteinases and Tissue Inhibitors Of Metalloprmentioning
confidence: 90%
See 3 more Smart Citations
“…Table 1 summarizes the polymorphisms of MMP genes that have been analyzed in AMD patients. Polymorphisms in MMP-1 (rs1799756) [30], MMP-3 (rs3025058) [26,32], and MMP-7 (rs11568818) [30,31] genes showed no statistical association with either the risk of AMD or disease progression.…”
Section: Matrix Metalloproteinases and Tissue Inhibitors Of Metalloprmentioning
confidence: 90%
“…Consequently, recent studies tried to keep in mind this global view of the pathogenesis, with hypothetical interrelations between different pathways. Budiene et al [30] investigated the relation of MMP polymorphisms with other gene polymorphisms and with their levels of mRNA and proteins in plasma. Oszajca et al [31] tried to analyze the possible association between MMP polymorphisms and the expression of some cytokines (IL-1β and IL-6), which have been found to be involved in the pathogenesis of AMD and are a possible crossing point of different pathways.…”
Section: Matrix Metalloproteinases and Tissue Inhibitors Of Metalloprmentioning
confidence: 99%
See 2 more Smart Citations
“…Using online search databases with keywords including "polymorphism", "age-related macular degeneration", and "meta-analysis", I summarized the findings from the latest published meta-analysis [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] as shown in Figure 1. Moreover, in this short communication additional meta-analysis of TNFα, CCL-2, MMP3, MMP7, MMP9, and TIMP2 were also included [19][20][21][22][23][24][25][26][27][28][29] . It was shown that a protective effect of TNFα -863A carrier (A vs C, OR = 0.67, P = 0.007; AA+CA vs CC, OR = 0.58, P = 0.001; CA vs AA+CC, OR = 0.55, P = 0.001; and CA vs CC, OR = 0.54, P = 0.001, Figure 2A-D) and TIMP2 -418C carrier (GC vs CC+GG, OR = 0.54, P = 0.018; and GC vs GG, OR = 0.56, P = 0.046, Figure 2E,F) to the development of AMD.…”
mentioning
confidence: 99%